2021
DOI: 10.3390/e23070890
|View full text |Cite
|
Sign up to set email alerts
|

Examining GDP Growth and Its Volatility: An Episodic Approach

Abstract: In this paper, we study economic growth and its volatility from an episodic perspective. We first demonstrate the ability of the genetic algorithm to detect shifts in the volatility and levels of a given time series. Having shown that it works well, we then use it to detect structural breaks that segment the GDP per capita time series into episodes characterized by different means and volatility of growth rates. We further investigate whether a volatile economy is likely to grow more slowly and analyze the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 86 publications
1
2
0
Order By: Relevance
“…Moreover, the average length of high growth episodes varies across the regions. On average, an episode of high growth lasts three years for firms in the US but reduces to two years for those firms headquartered in Japan and Europe, a finding consistent with the literature (Bartak et al, 2021; Monteiro, 2019). Additionally, the findings on Japanese and EU firms confirm the episodic nature of the high growth episodes in these regions (World Bank, 2019).…”
Section: Theoretical Backgroundsupporting
confidence: 88%
“…Moreover, the average length of high growth episodes varies across the regions. On average, an episode of high growth lasts three years for firms in the US but reduces to two years for those firms headquartered in Japan and Europe, a finding consistent with the literature (Bartak et al, 2021; Monteiro, 2019). Additionally, the findings on Japanese and EU firms confirm the episodic nature of the high growth episodes in these regions (World Bank, 2019).…”
Section: Theoretical Backgroundsupporting
confidence: 88%
“…For instance, Kim, Lin, and Suen (2016) found that trade openness enhances growth stability in the short run, but it eventually contributes to lower output stability in the long run in cross-countries [41]. The results above were further confirmed by the studies of Udeagha and Ngepah (2021) and Bartak et al (2021) [16,40]. In particular, they additionally examined the nonlinear relationship and concluded that higher trade openness hampers economic growth, whereas lower trade openness induces increases in economic growth in the long run.…”
Section: Introductionmentioning
confidence: 68%
“…First, even though the stories of flourishing economic growth of Asia countries conveyed the importance of trade openness policies [9], until now, no study covered the whole Asia region related to the relationship between trade openness and economic growth. According to our knowledge, the literature regarding the relationship between trade openness and economic growth focused mostly on developed countries [32,33,[35][36][37][38], or cross economies [39][40][41][42][43]. As for the Asian region, only several particular Asia countries were studied separately, i.e., Malaysia [44][45][46]; Pakistan and India [47,48], or several South Asian countries [49].…”
Section: Introductionmentioning
confidence: 99%
“…On this basis, we identify episodes with different growth rates and different volatility. We choose the genetic algorithm rather than the Bai-Perron algorithm (reckoned as a standard procedure in this area of study), because it outperforms the Bai-Perron method in two ways [25]:…”
Section: Data and Resultsmentioning
confidence: 99%